2015
DOI: 10.1016/j.plasmid.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification, sequencing and comparative analysis of pBp15.S plasmid from the newly described entomopathogen Bacillus pumilus 15.1

Abstract: The Bacillus pumilus 15.1 strain, a recently described entomopathogenic strain active against Ceratitis capitata, contains at least two extrachromosomal elements, pBp15.1S and pBp15.1B. Given that B. pumilus is not a typical entomopathogenic bacterium, the acquisition of this extrachromosomal DNA may explain why B. pumilus 15.1 is toxic to an insect. One of the plasmids present in the strain, the pBp15.1S plasmid, was sub-cloned, sequenced and analyzed using bioinformatics to identify any potential virulence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 66 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…The acridine orange strain was selected for further studies and named B. pumilus 15.1C (cured from plasmid (pBp15.1S) and megaplasmid (pBp15.1B)). As, in contrast to the megaplasmid, the smaller pBp15.1S plasmid has been completely characterized, and its copy number was found to be 33 (Garcia‐Ramon et al ., ), we were able to verify its absence by PCR since, using the same methodology: no amplification was obtained from B. pumilus strain 15.1C (data not shown). Southern blot analysis using a Dig‐labelled probe designed in the orf 7 of the plasmid pBp15.1S was also carried out.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The acridine orange strain was selected for further studies and named B. pumilus 15.1C (cured from plasmid (pBp15.1S) and megaplasmid (pBp15.1B)). As, in contrast to the megaplasmid, the smaller pBp15.1S plasmid has been completely characterized, and its copy number was found to be 33 (Garcia‐Ramon et al ., ), we were able to verify its absence by PCR since, using the same methodology: no amplification was obtained from B. pumilus strain 15.1C (data not shown). Southern blot analysis using a Dig‐labelled probe designed in the orf 7 of the plasmid pBp15.1S was also carried out.…”
Section: Resultsmentioning
confidence: 87%
“…The majority of crystal toxin genes of Bt are encoded on extrachromosomal elements, and we decided to investigate the location of the oxdD gene. We have recently shown that the B. pumilus 15.1 strain bears one plasmid of 7785 bp named pBp15.1S (Contig 38) and one megaplasmid of unknown size named pBp15.1B (Garcia‐Ramon et al ., ). The oxdD gene was found in Contig 4 (Accesion number ), a contig of 57 329 bp that encodes 51 predicted proteins.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations